Clinical manifestations and longterm followup of a patient with CINCA/NOMID syndrome - Ebrahimi-Fakhari, Darius; Wahlster, Lara; Mackensen, Friederike; Blank, Norbert (The journal of rheumatology, 2010)
Chronic infantile neurological cutaneous and articular (CINCA) syndrome1 is a rare, genetic autoinflammatory disease that belongs to the spectrum of cryopyrin-associated periodic syndromes (CAPS), along with the familial cold autoinflammatory syndrome and the Muckle-Wells syndrome. CAPS are associated with autosomal-dominant mutations in the NLRP3 gene (formerly CIAS1), which encodes the protein cryopyrin2,3. Within the spectrum of CAPS, the CINCA syndrome, also known as neonatal-onset multisystem inflammatory disease (NOMID), is considered to be the most severe phenotype. A triad of urticarial rashes, neurological manifestations, and arthropathy, accompanied by recurrent fever episodes and systemic inflammation, originally defined CINCA syndrome1,4. Systemic AA-amyloidosis is a serious longterm complication that can lead to renal failure and increased mortality4.